南北両極氷床コアに眠る菌類 - 辻, 雅晴; 中澤, 文男; 伊村, 智; Masaharu, Tsuji; Fumio, Nakazawa; Satoshi, Imura (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object